EKSEKUSI PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA DI ERA PANDEMI (TELAAH KAJIAN MASLAHAH MURSALAH) - Rofiqi, Imam; Rusfandi, Rusfandi; Anita, Anita (Fakultas Hukum Universitas Wiraraja, 2023)
The government has a program for small entrepreneurs in terms of activating the provision of credit to weak economic groups for the welfare of people's lives. Credit granting programs with a Fiduciary system can help credit recipients and credit providers. If the guarantee right can be executed quickly with a simple, efficient process and contains legal certainty, this is one of the parameters of a material debt guarantee. This research method uses the Juridical Empirical method, which is an approach taken to analyze the effectiveness of a regulation/legislation or existing law. In this case the approach is used to analyze qualitatively the implementation of fiduciary guarantees in Indonesia. This study uses primary data, namely data obtained directly from the field through an interview process and secondary data, namely examining various legal materials through library research. The analysis used in this research is qualitative analysis which draws conclusions using deductive analysis. Fiduciary Guarantee Law Number 42 of 1999 regulates the execution of Fiduciary Guarantees in Indonesia where there are various variations of the execution, therefore the parties can choose which execution model they want. However, in practice how to carry out the execution of fiduciary guarantees when there are problem loans, many still do not know, especially the implementation in pawnshops, which in fact have just handled the fiduciary system installment credit program. Which model is used by creditors throughout Indonesia. It is hoped that by knowing the system, model or method of executing fiduciary guarantees in this study, people will know more about the ins and outs, their rights and the consequences when taking credit with fiduciary system installments to creditors.